2023
DOI: 10.3390/molecules28031090
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Phototoxic Effects of Cationic Porphyrins on Human Cells In Vitro

Abstract: The toxic effects of four cationic porphyrins on various human cells were studied in vitro. It was found that, under dark conditions, porphyrins are almost nontoxic, while, under the action of light, the toxic effect was observed starting from nanomolar concentrations. At a concentration of 100 nM, porphyrins caused inhibition of metabolism in the MTT test in normal and cancer cells. Furthermore, low concentrations of porphyrins inhibited colony formation. The toxic effect was nonlinear; with increasing concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Importantly, the prepared hydrogels did not show any cytotoxic effect on the NIH3T3 fibroblasts without light irradiation. This observation aligns with the findings reported in the literature, namely that in the absence of light, cationic porphyrins exhibit negligible cytotoxicity on various human cell lines [51]. Both cytocompatibility and degradability are critical characteristics of hydrogels that determine the efficacy of topical applications, for example, in wound healing [52].…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, the prepared hydrogels did not show any cytotoxic effect on the NIH3T3 fibroblasts without light irradiation. This observation aligns with the findings reported in the literature, namely that in the absence of light, cationic porphyrins exhibit negligible cytotoxicity on various human cell lines [51]. Both cytocompatibility and degradability are critical characteristics of hydrogels that determine the efficacy of topical applications, for example, in wound healing [52].…”
Section: Discussionsupporting
confidence: 90%
“…Studies suggest that irradiation with blue light inhibits tumor growth in various cancer cell lines through diverse mechanisms [ 27 - 34 ]. In the context of photoreceptors, Ohara et al reported that blue light (λ = 470 nm, irradiance 5.7 mW/cm 2 ) inhibited the growth of B16 melanoma cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zarska et al also evaluated the photodynamic effect of α, β, γ, δ-tetrakis (1-methylpyridinium-4-yl) porphyrin p-toluenesulfonate (TMPyP) and zinc-4-sulfonatophenyl porphyrin (ZnTPPS4) on the HeLa (cervical cancer) and G361 (human skin malignant melanoma) cell lines with blue light (λ = 414 nm) irradiation [ 32 ]. Yegorov et al recently reported the toxicity of blue light with porphyrins (cationic porphyrin P4 (TMPyP4) and its amphiphilic derivative porphyrin P1 containing carboxyl groups, as well as their zinc-containing analogues ZnP4 and ZnP1) in normal (human mesenchymal stromal cells KO-16, an immortalized human embryonic fibroblast line (977-hTERT)) and cancer cells (A549 and SK-N-SH) [ 34 ]. They demonstrated that in the presence of blue light for 30 min of irradiation, there was a significant decrease in the viability of all cell lines (concentrations 50 nM).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the biocompatibility of Col and Col-LF membranes in vitro, they were tested with two cell lines: keratinocytes (HaCaT line) and fibroblasts (977hTERT embryonic fibroblasts [52]). Cells were cultured using growth medium of the following composition: DMEM/F12 (1:1, BioloT, Saint Petersburg, Russia), gentamicin (50 µg/mL, PanEco, Moscow, Russia), and fetal calf serum FBS (10%, ThermoFisher, Waltham, MA, USA).…”
Section: Biocompatibility Tests In Vitromentioning
confidence: 99%